Single stage electrospun multicomponent scaffold for bone tissue engineering application - Jaganathan, Saravana Kumar (Elsevier Ltd, 2018)
Incorporation of oils in to the polymer matrix results in the improvement of physicochemical and biocompatible properties. A novel polyurethane based composite bone scaffold was fabricated by electrospinning using sunflower and neem oil for the first time. Scanning electron microscopy (SEM) revealed the mean fiber diameter of the electrospun nanocomposite was decreased with the addition of sunflower oil (816 ± 129.54 nm) and sunflower/neem oil (739 ± 130.922 nm) into the PU matrix (890 ± 116.9115 nm). The strong interactions between PU, sunflower oil and neem oil were observed through Fourier transform infrared spectroscopy (FTIR) and thermogravimetric analysis (TGA). Contact angle analysis depicted the hydrophobic (PU/sunflower oil - 112° ± 1) nature and with the incorporation of neem oil it shifted to hydrophilic (PU/sunflower oil/neem oil - 61.67° ± 2.517) behavior. Further, the tensile strength analysis showed the improvement in the mechanical strength with the addition of sunflower oil (10.62 MPa) and sunflower/neem oil (11.67 MPa) in to the PU matrix (7.12 MPa). In addition, the developed composites exhibited reduced hemolytic index percentage and enhanced blood clotting time through coagulation studies. Moreover, the cytocompatibility investigation revealed the non-toxic nature of the fabricated nanocomposites with human dermal fibroblast (HDF) cells than the pristine PU. Hence, the developed PU based composites rendering better physio-chemical and cytocompatible properties can serve as an alternate substitute for bone tissue engineering applications.